Underlying Mechanism of Wild Radix pseudostellariae in Tolerance to Disease Under the Natural Forest Cover - Wu, Hongmiao; Xia, Jinshen; Qin, Xianjin; Wu, Huiming; Zhang, Shengkai; Zhao, Yanlin; Rensing, Christopher; Lin, Wenxiong (Frontiers in Microbiology, 2020)
Replanting disease caused by negative plant-soil feedback in continuous monoculture of Radix pseudostellariae is a critical factor restricting the development of this common and popular Chinese medicine, although wild R. pseudostellariae plants were shown to grow well without occurrence of disease in the same site for multiple years. Therefore, we aimed to identify the changes in microbial community composition in the rhizosphere soil of wild R. pseudostellariae thus providing a potential method for controlling soil-borne diseases. We analyzed differences in soil physicochemical properties, changes in soil microbial community structure, and root exudates of wild R. pseudostellariae under different biotopes. And then, SSR (simple sequence repeats) amplification was used to isolate and collect significantly different formae speciales of F. oxysporum. Finally, we analyzed the pathogenicity testing and influence of root exudates on the growth of F. oxysporum. We found that the different biotopes of R. pseudostellariae had significant effects on the soil microbial diversity. The soil fungal and bacterial abundances were significantly higher and the abundance of F. oxysporum was significantly lower under the rhizosphere environment of wild R. pseudostellariae than under consecutive monoculture. The relative abundances of most genera were Penicillium, Aspergillus, Fusarium, Nitrobacter, Nitrospira, Streptomyces, Actinoplanes, and Pseudomonas. Venn diagram and LEfSe analyses indicated numerously specific microbiome across all the samples, and the numbers of specific fungi were higher than the shared ones in the four biotopes. Eight types of phenolic acids were identified across all the rhizosphere soils. Mixed phenolic acids and most of the examined single phenolic acids had negative effects on the growth of isolated pathogenic F. oxysporum strains and promoted the growth of non-pathogenic strains. Similarly, correlation analysis suggested that most of the identified phenolic acids were positively associated with beneficial Pseudomonas, Nitrobacter, Nitrospira, Streptomyces, and Bacillus. This study suggested that wild R. pseudostellariae was able to resist or tolerate disease by increasing soil microbial diversity, and reducing the accumulation of soil-borne pathogens.